Candidiasis During Pregnancy May Result From Isogenic Commensal Strains. Issue 2 (2001) - Daniels, Wayne; Glover, Douglas D.; Essmann, Michael; Larsen, Bryan
Abstract : Objective: Our laboratory previously demonstrated that asymptomatic vaginal colonization during pregnancy is a factor predisposing patients to subsequent symptomatic vulvovaginal candidiasis. It is unknown whether symptoms result from strain replacement or a change in host relationship to the original colonizing strain. This study was undertaken to determine whether Candida albicans isolates from asymptomatic women could be responsible for subsequent symptomatic vaginitis. Methods: We retained isolates of C. albicans from women followed longitudinally through pregnancy, and identified six pairs of cultures from women who were colonized without symptoms and who later became symptomatic (average time 14 weeks). We used a random amplification of polymorphic DNA (RAPD) analysis to determine whether isolates from our study patients were genetically similar or dissimilar. Results: Analysis of these pairs of yeast strains by RAPD revealed that five of the six women had symptoms apparently due to the same yeast strain that was found initially as a commensal strain. To increase the power of these observations, we also performed RAPD analysis on six randomly selected yeast strains from other women in this study who had not become symptomatic to determine whether any of these unrelated strains matched strains from those women who became symptomatic. Conclusion: Symptomatic yeast vaginitis is usually due to strains of C. albicans already carried in the lower genital tract, underscoring the need to understand regulation of growth and virulence of the organism in vivo .